Asuhan Kebidanan Komprehensif Pada Ny “M” Di Puskesmas Sindanglaut - Pipit Indra L (Awatara Publisher, 2026)
Comprehensive midwifery care is a continuous service provided from pregnancy, childbirth, postpartum, newborn care, to family planning, which plays an important role in improving maternal and neonatal health and reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). This case study aimed to implement comprehensive midwifery care for Mrs. “M” G5P4A0 with a gestational age of 38 weeks and 5 days at Sindanglaut Public Health Center during February–May 2025. This case report used a descriptive method with a continuity of care approach. Data were collected through interviews, observations, and documentation of midwifery care using the SOAP format. The care provided included two antenatal visits, one delivery care, four postpartum visits, three newborn visits, and one family planning service. The results showed that during pregnancy, the mother had no complaints. The delivery occurred normally at 38 weeks and 5 days of gestation without complications. The baby was born spontaneously on March 20, 2025, at 14:24 WIB, female, with a strong cry, a birth weight of 3,445 grams, and a body length of 50 cm. During the postpartum period and newborn care, no complaints or complications were identified. After the postpartum period, the mother chose an implant contraceptive method with a three-year duration. In conclusion, comprehensive midwifery care for Mrs. “M” was implemented optimally, with no gaps or danger signs identified in the mother or the newborn